2016
DOI: 10.1016/j.celrep.2016.02.090
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Inhibition Corrects Neurodevelopmental and Synaptic Alterations in a Human Stem Cell Model of Tuberous Sclerosis

Abstract: Hyperfunction of the mTORC1 pathway has been associated with idiopathic and syndromic forms of autism spectrum disorder (ASD), including tuberous sclerosis, caused by loss of either TSC1 or TSC2. It remains largely unknown how developmental processes and biochemical signaling affected by mTORC1 dysregulation contribute to human neuronal dysfunction. Here, we have characterized multiple stages of neurogenesis and synapse formation in human neurons derived from TSC2-deleted pluripotent stem cells. Homozygous TSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
120
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(140 citation statements)
references
References 44 publications
20
120
0
Order By: Relevance
“…Notably, we detected mTORC1 activation in TSC2 +/− iPSC-derived neurons (M-J.H. and M.S., unpublished), similar to recently published observations of mTORC1 hyperfunction in TSC2 +/− human embryonic stem cell-derived neurons (Costa et al, 2016). …”
Section: Resultssupporting
confidence: 91%
“…Notably, we detected mTORC1 activation in TSC2 +/− iPSC-derived neurons (M-J.H. and M.S., unpublished), similar to recently published observations of mTORC1 hyperfunction in TSC2 +/− human embryonic stem cell-derived neurons (Costa et al, 2016). …”
Section: Resultssupporting
confidence: 91%
“…In line with previous studies, patch clamp recordings from 16pdel neurons showed intrinsic electrical properties consistent with their larger size, i.e., increased C m , decreased R inp and reduced excitability(Costa et al, 2016; Williams et al, 2015). Based on increased dendrite length of 16pdel neurons, we would predict increased number of synapses on the dendrites.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, loss of TSC2, which inhibits mTOR, an effector of the PI3K/AKT pathway, often results in macrocephaly associated with ASD, ID and seizures. Loss of TSC2 in human iPSC-derived neurons results in increased soma size, dendritic arborization and total dendrite length (similar to our observations in 16pdel) mediated by a hyperactive PI3K/AKT pathway(Costa et al, 2016). The 16p11.2 region harbors genes encoding proteins that are known to interact with the PI3K/AKT or Ras/MAPK pathway, hence it may affect cellular phenotypes in a dosage-dependent manner via this interaction.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…First, we did not investigate further the link between mTOR hyperactivation and synaptic transmission and plasticity, which might influence neuronal excitability and trigger epileptogenesis. However, a recent study on neurons derived from TSC2 -deleted pluripotent stem cells demonstrated that heterozygous and homozygous loss of TSC2 led to altered synaptogenesis and transmission and that pharmacological inhibition of mTORC1 could ameliorate synaptic dysfunction (Costa et al., 2016). Second, only the proband who was carrying TSC2 gene mutation was compared with the normal control subject in our study.…”
Section: Discussionmentioning
confidence: 99%